"Can you dance for me?" the (Im)possibility of speaking trauma in dance ethnography. Issue 3 (2nd October 2021) - Oh, Chuyun
ABSTRACT: This article analyzes my six-year autoethnographic work in response to From Silence to Power in Austin, TX from 2013 to 2019. Performed by survivors of sexual abuse, the performance externalized trauma, recognized time via repetition, re-contextualized their minded-bodies and transformed from silenced victims to survivors. Kinesthetic empathy moved me to work through my trauma as a co-performer. I have written performance reviews, given three conference presentations and performed an autoethnography Dancethnography in TX, NY, MD, PA, and CA. This project evolved from ethnography on others, to autoethnography and to reverse ethnography through which I witness (im)possibilities of dance in speaking trauma due to decorative virtuosity.